2018
DOI: 10.1097/icl.0000000000000532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Q-Adjusted LASIK and Small-Incision Lenticule Extraction for Correction of Myopia and Myopic Astigmatism

Abstract: SMILE is as safe and predictable as FS-LASIK. According to the ORA system, SMILE is not better than FS-LASIK in terms of biomechanical changes. However, SMILE causes less effect on dry eye parameters during the first 3 postoperative months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Seventeen studies reported a cap thickness between 100 to 120 μ m [25, 30, 3941, 45, 4753, 55, 56, 58, 59]. Only one study reported a 90 μ m thickness cap [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies reported a cap thickness between 100 to 120 μ m [25, 30, 3941, 45, 4753, 55, 56, 58, 59]. Only one study reported a 90 μ m thickness cap [36].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported a 90 μ m thickness cap [36]. The cap diameter was between 7.2 to 8 mm in 16 studies, [25, 30, 36, 38, 41, 4551, 53, 5860] and the diameter of the optical zone was between 6 to 7 mm in 19 studies [25, 30, 36, 3841, 45, 4749, 5156, 58, 59]. Twelve studies were performed with an energy between 115 to 190 nJ [30, 36, 38, 40, 41, 45, 47, 4951, 53, 54, 58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekundo et al [1] first introduced this new procedure in 2011. e first clinical study [2] of femtosecond lenticule extraction in China was also reported in 2011. Numerous clinical studies [3][4][5][6][7][8][9] suggested that SMILE is a safe and effective procedure for myopia correction, and the follow-up periods in these studies mostly spanned from 3 months to 3 years, but rarely up until 4 years [10][11][12][13][14]. In 2019, we [15] have previously compared the 5-year outcomes of SMILE and femtosecond laser-assisted LASIK (FS-LASIK) in patients with myopia.…”
Section: Introductionmentioning
confidence: 99%
“…However, Wenjing WU et al [15] and Elmohamady et al [16] found that CH and CRF both exhibited postoperative differences between the SMILE group and the FS-LASIK group. Lei Xia et al [17] and El-Mayah E et al [18] concluded that while there was no significant difference in the postoperative CH between the SMILE group and the FS-LASIK group, the postoperative CRF was different between the two groups. Therefore, we performed this meta-analysis to clarify whether CH and CRF were different after the surgery in the SMILE and FS-LASIK groups.…”
Section: Discussionmentioning
confidence: 99%